THE ETHNOSCIENCE OF BREM IN WONOGIRI AND ITS INTEGRATION IN SCIENCE LEARNING: AN EXPLORATORY STUDY - Arief Setyo Nugroho; Agustina Wahyuningsih; Retno H; Anatri Desstya; Yulia Maftuhah Hidayaati (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2023)
The educational paradigm has tried to create a quality of education that is in line with current developments but still does not forget the character of students and the local wisdom culture of the local area. The relationship between culture and the application of science in society is studied using an ethnoscience approach. The ethnoscience approach in science learning is an approach that is expected to help students think critically and explore phenomena that occur in the environment around them. This study aims at 1) Exploration of making “brem” in Wonogiri Regency; 2) Integrating Ethnoscience in the “brem” manufacturing industry in the Basic Competencies of Elementary School Science Learning. The study was included in qualitative methods of ethnographic design by determining both material and formal research objects. Research data was collected through interview techniques, observation and documentation of primary and secondary data. Through inductive data analysis techniques with data reduction processes and data presentation, it is assumed that reliable conclusions can be drawn. The research results show that the process of making “brem” goes through many processes and stages. The process of making Wonogiri “brem” applies science knowledge which can be compared with scientific expert statements. In conclusion, the process of making g of Wonogiri “brem” has gone through a scientific process, both chemical and biological reactions. Another conclusion is that process of making “brem” can be integrated as meaningful teaching material for students in several Basic Competencies in science lesson content for grades 3 and 5 of elementary school.